Electricity Supply in Nigeria: Cost Comparison between Grid Power Tariff and Fossil-Powered Generator - Babatunde, Olubayo Moses; Ayegbusi, Clement Olaniyi; Babatunde, Damilola Elizabeth; Oluseyi, Peter Olabisi; Somefun, Tobilola Emmanuel (International Journal of Energy Economics and Policy, 2020)
Electricity supply in Nigeria is a huge problem with great economic and political consequences. After unbundling and privatization of generation and distribution companies, not much improvement has been experienced by electricity consumers; this is due to lack of investment in infrastructure. Lack of investment in infrastructure especially from private investors is caused largely by non-cost reflective tariff among other factors highlighted in this study. While many believe tariff has to be controlled such that it does not go beyond the reach of average citizens, many also believe that the average citizens can pay much more than the current tariff. The latter is evident considering the average amount spend on the use of portable gasoline generators by most homes and small enterprises both in rural and urban centers. The whole life cost method is used to show here that it costs a home or business premise that operates a portable gasoline generator for 6 hours daily NGN 37, 000 per month and costs NGN 157,000 to operate 20 kVA diesel generator. This shows the consumers' capacity to pay the appropriate tariff that can attract investors to the sector. Keywords: Utility, tariff, electric power generation cost, life cost method, consumer JEL Classification: Q43 DOI: https://doi.org/10.32479/ijeep.8590